Peningkatan Profesionalisme Guru Raudhatul Athfal - Zahroh, Luluk Atirotu (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
Raudhatul Athfal (RA), an Islamic kindergarten, is a kind of early education which aims at education children from newly born till the age of six years. The purpose of such kind of education is to provide stimulation and assist the development of children’s physical and spiritual aspect. RA teachers, therefore, must be professional and professionalism must be developed continuously. The biggest challenge of RA teacher professionalism is the advancement of science and technology.